Estudo dos métodos de projeto de fábrica e sua aplicação no setor público de serviços: estudo de caso em escolas de educação infantil. - Guerreiro, Érico Daniel Ricardi (2004)
This work contributes for the project and planning of children s schools, searching a project method that it makes possible to structuralize the facilities in function of the carried through productive activities. The objective is to analyze the use of the for facilities planning methods, into project of children s schools, its viability, effectiveness, necessity and particularity. This analisys objective to conceive children s schools through a scientific method that guarantees of its productive performance. Initially it is made a study of existing methods of facilities planning, its content and its applications, for election of a method that better get adapted to the project of children s schools. Also a study on the children education is carried through, service that guides the planning of the object of this study, children s schools. Beyond these, a study is become fulfilled on the inquiry of the activity of work, that will guide the practical ones of inquiry of the chosen object for this study. After the chosen method, a study of case in a school on the São Carlos City to prove the application of the method, its necessity and efficiency. One result identified was the lack of knowledge of the demand and its characteristics to it in the city, a determination of the installations on the services and a series of particularities for the application of the method in schools it was also verified that the application of the project method chosen is viable and necessary for the construction of children s schools.